The impact of physician’s decentralization on health services and economic growth - COÊLHO, André Luiz Ribeiro Coutinho Berardo de Moraes (2017)
This research uses the Zon and Muyken (2001) model to investigate the effect of physicians’ decentralization of health care production, human capital accumulation, and economic growth. All three sectors are interrelated, since the overall level of health affects both workers and the accumulation of human capital, while a higher level of human capital is related to better quality of health. And, finally, health and human capital affect the output of the economy. From the economic growth point of view, the results seem to be positive. The physician’s decentralization from denser municipalities to smaller ones impacts the health and wellbeing of the population positively overall. It’s important to point out the necessity of a public policy that may be able to allocate the physicians throughout the country more efficiently, the suggested proposal is federal public tender for the physicians. Increasing physicians per inhabitant availability in municipalities of the North and Northeast, South and Southeast regions with a population above or below fifty thousand inhabitants, raises productivity in the health sector. This increase ultimately improves labor productivity, resulting in increased capital accumulation and economic growth. On the other hand, it is estimated a reduction in the propensity to consume when there is a smaller portion of the labor force allocated in the health sector.